2004
DOI: 10.1038/modpathol.3800167
|View full text |Cite
|
Sign up to set email alerts
|

Novel endothelial cell markers in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is characterized by hypervascularity and a propensity for vascular invasion. Detailed analysis of complementary DNA (cDNA) microarray global gene expression data and further validation on a smaller independent sample set by reverse transcription-polymerase chain reaction established the presence of two endothelial gene clusters in hepatocellular carcinoma. Cluster I, consists of 20 cDNA clones, representing 15 unique genes. Cluster II consists of nine unique genes. The expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…Immunohistochemical staining was performed on liver tissue sections using DAKO envision plus kit (DakoCytomation, Carpinteria, CA) as described previously. 42 Cell proliferation assays. To test for cyclopamine responsiveness, HCC cell lines were grown for five days in control medium or medium containing DMSO/ethanol (50:50, v/v), or containing tomatidine (10 µM), or containing cyclopamine (10 µM).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining was performed on liver tissue sections using DAKO envision plus kit (DakoCytomation, Carpinteria, CA) as described previously. 42 Cell proliferation assays. To test for cyclopamine responsiveness, HCC cell lines were grown for five days in control medium or medium containing DMSO/ethanol (50:50, v/v), or containing tomatidine (10 µM), or containing cyclopamine (10 µM).…”
Section: Methodsmentioning
confidence: 99%
“…The hybridization probes for Spry2 were prepared as previously described (22) and used in nonradioactive in situ hybridization as detailed in Chen et al (28). Arrays were scored using a four-tier scale: 0, negative; 1, insufficient or equivocal; 2, weak staining; 3, strong staining.…”
Section: Methodsmentioning
confidence: 99%
“…Integrins are a family of transmembrane receptors and SPP1 is a ligand of integrin α V β 3 , which is a combination of integrin subunit α V and β 3 . RGS5 has been reported to be a marker of cancer-associated endothelial cells (15) and is an endothelial cell marker that is highly expressed in HCC (16). Therefore, ITGB3, SPP1, RGS5, MT1 G and MT1H were focused on by the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Silini et al (15) reported higher levels of RGS5 mRNA in endothelial cells isolated from carcinomas, primarily ovarian carcinomas, compared with endothelial cells isolated from non-neoplastic tissue. In a study of hepatic tissue, Chen et al (16) used ISH to demonstrate that RGS5 was not expressed in sinusoidal endothelial cells in non-tumor liver tissues, detected RGS5 mRNA in the sinusoidal endothelial cells in the HCC samples. The present study used immunohistochemical staining to reveal that RGS5 was expressed in the cytoplasm of HCC cells.…”
Section: Discussionmentioning
confidence: 99%